SAFETY IMPROVEMENT THOUGHTS IN MINING INDUSTRIES - Rao, G. Nageswara (International Journal of Research -GRANTHAALAYAH, 2018)
Mining industry associated with many type of technical involvement i.e. from low to high and run by unskilled, semi-skilled, skilled and technically skilled manpower oriented. The efficiency of this industry is mainly depending on safety of work force. Productivity is proportionate to safety of workmen, machinery and working site etc. The safety is better in the mine then it gets best productivity. The accident analysis in mining industry reveals that prime cause is lack of personal safety. When the safety thoughts roaming in the minds of work force as well as in management will always make the industry way leading to safe so that personal safety also good. The personal safety of workmen is influenced by internal and external agencies of behavioral attitude stress that is at home and at work site. In this paper explained some of safety tips particularly on personal safety matters inside and outside of the work site and behavioral attitude required for work force towards achieving goal of industry motive towards reach of Zero Hazardous, Zero Incidents and Zero losses.